2017
DOI: 10.1111/edt.12340
|View full text |Cite
|
Sign up to set email alerts
|

The risk of healing complications in primary teeth with extrusive or lateral luxation—A retrospective cohort study

Abstract: The healing potential for laterally luxated teeth was high and more than half of the extruded teeth, which were repositioned after injury, showed long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 22 publications
(47 reference statements)
2
34
0
10
Order By: Relevance
“…Pulp canal obliteration was reported in five of the six studies. The combined data from these studies show that 31.3% of immature teeth presented with pulp canal obliteration following lateral luxation injuries . Pulp necrosis was also reported in five of the six studies.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Pulp canal obliteration was reported in five of the six studies. The combined data from these studies show that 31.3% of immature teeth presented with pulp canal obliteration following lateral luxation injuries . Pulp necrosis was also reported in five of the six studies.…”
Section: Resultsmentioning
confidence: 82%
“…Pulp necrosis was also reported in five of the six studies. The prevalence of pulp necrosis in laterally luxated immature teeth was 17.5% . Lin et al and Hevoca et al reported internal root resorption and it was estimated to affect only 0.9% of teeth .…”
Section: Resultsmentioning
confidence: 98%
“…15 Another retrospective study involved 331 primary teeth with lateral luxation left without treatment. 34 It found that the estimated risks after three years for pulpal canal obliteration (PCO) were 41.3%, pulpal necrosis (PN) 19.8%, infection related resorption (IRR) 7.0%, ankylosis related resorption (ARR) 1.4% and premature tooth loss as 24.8%. 35 This study concluded that conservative management was associated with a relatively high healing potential.…”
Section: Lateral Luxationmentioning
confidence: 99%
“…35 This study concluded that conservative management was associated with a relatively high healing potential. 34 On the other hand, in laterally luxated teeth with severe occlusal interferences, leaving the tooth to spontaneously reposition may further compromise its prognosis. 36 If there is minor occlusal interference as a result of lateral luxation, slight odontoplasty is advocated, as per the IADT guidelines.…”
Section: Lateral Luxationmentioning
confidence: 99%
“…Até o presente momento, a literatura apresenta estudos que demostram a incidência da reabsorção radicular externa patológica em dentes decíduos traumatizados e alguns de seus fatores associados Andreasen, 1998;Holan, 2004;Rocha, 2008;Santos et al, 2011;Holan;Yodko, 2015;Lauridsen et al, 2017a;Lauridsen et al, 2017b;Lauridsen et al, 2017c), porém até o presente momento não há na literatura estudos que avaliem a influência destas reabsorções no ciclo fisiológico do incisivo superior decíduo traumatizado.…”
Section: Seleçãounclassified